Using birds in environmental impact assessment of quarrying activities: a case study in the Atlantic forest of Southern Brazil - Cleiton D. Teixeira; Marcéli D. S. Lopes; Teixeira, Douglas D.; Caio José Carlos (Acta Biológica Catarinense, 2025)
The use of environmental indicators in Environmental Impact Assessments (EIA) is a common approach to evaluate the ecological quality of a given area. Birds are particularly valuable as bioindicators in the Atlantic forest, especially in the context of mining activities such as quarrying. This study aimed to (1) estimate the magnitude of environmental impacts; (2) provide data to assess their significance; (3) predict future environmental conditions under the proposed project; and (4) support the comparison of alternatives and the development of mitigation strategies. A systematic literature review was conducted using the Web of Science and Google Scholar platforms. When refined to focus on birds, 25 impacts across 14 environmental aspects were identified, of which four were considered positive and the remainder negative. The impact-aspect matrix revealed that most negative effects on bird communities are associated with the installation and extraction phases of quarry operations. In contrast, positive impacts were linked to the recovery of degraded areas, which can promote the establishment of new habitats. These findings highlight the importance of integrating avian data into EIA processes to inform decision-making and enhance the ecological sustainability of mining projects.